ANALYSIS OF NEEDS FOR THE NUMBER OF EMPLOYEES BASED ON WORKLOAD CALCULATIONS IN THE COMPANY MEDAN CITY MARKET AREA - Dicky Habibie; Nazaruddin; Yeni Absah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The aim of this research is to determine and analyze the number of employees and workload available in work units (sections, sections or departments) at PD Pasar Kota Medan. This research is quantitative research. According to (Arikunto 2019:27) quantitative research is a research method that, as the name suggests, requires a lot of use of numbers, starting from data collection, interpretation of the data, and the appearance of the results. The sampling technique in this research is the Simple Random Sampling Method. Simple Random Sampling "is taking sample members from a population randomly without paying attention to the strata in that population. The results of the research show that Job Analysis found that in general employee workload is underloaded, only 1 market is overloaded, but there is no need for additional employees. This shows that there is no need to increase the number of PD Pasar Kota Medan employees. Meanwhile, if we look at the Market Units, of the 18 Market Units there are 16 Market Units that are underloaded, 1 Market Unit that is overloaded and 1 Market Unit that is inloaded.